Molecular Epidemiology of HIV-1 Subtype B Reveals Heterogeneous Transmission Risk: Implications for Intervention and Control. (26th February 2018) - Volz, Erik M; Le Vu, Stephane; Ratmann, Oliver; Tostevin, Anna; Dunn, David; Orkin, Chloe; O'Shea, Siobhan; Delpech, Valerie; Brown, Alison; Gill, Noel; Fraser, Christophe; ,
Abstract : Young men who have sex with men (MSM) in the United Kingdom have greater risk of infection and higher risk of transmission to other young MSM, which has implications for design of pre-exposure prophylaxis public health initiatives. Abstract: Background: The impact of HIV pre-exposure prophylaxis (PrEP) depends on infections averted by protecting vulnerable individuals as well as infections averted by preventing transmission by those who would have been infected if not receiving PrEP. Analysis of HIV phylogenies reveals risk factors for transmission, which we examine as potential criteria for allocating PrEP. Methods: We analyzed 6912 HIV-1 partial pol sequences from men who have sex with men (MSM) in the United Kingdom combined with global reference sequences and patient-level metadata. Population genetic models were developed that adjust for stage of infection, global migration of HIV lineages, and changing incidence of infection through time. Models were extended to simulate the effects of providing susceptible MSM with PrEP. Results: We found that young age <25 years confers higher risk of HIV transmission (relative risk = 2.52 [95% confidence interval, 2.32–2.73]) and that young MSM are more likely to transmit to one another than expected by chance. Simulated interventions indicate that 4-fold more infections can be averted over 5 years by focusing PrEP on young MSM. Conclusions: Concentrating PrEP doses on young individuals can avert more infections than random allocation.